2012
DOI: 10.1093/annonc/mdr065
|View full text |Cite
|
Sign up to set email alerts
|

Sunitinib followed by sorafenib or vice versa for metastatic renal cell carcinoma—data from the Czech registry

Abstract: In contrast to most of the previously published reports, we have not observed improved PFS or OS for mRCC patients treated with the sorafenib-sunitinib sequence as compared to the sunitinib-sorafenib sequence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 17 publications
3
38
0
Order By: Relevance
“…[13, [20][21][22][23] Clinical trials investigating the use of sequential treatment strategies in mRCC have shown that single targeted agents can cause tumor shrinkage, slow disease progression and demonstrate significant PFS and QoL benefits. [18,24,25] The benefit of targeted therapy second line and beyond in patients with mRCC has been demonstrated through the analysis of data from 2705 patients, obtained from the International mRCC Database Consortium, which indicated that patients who are able to receive more lines of targeted therapy live longer than those who receive fewer.…”
Section: Expert Opinionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13, [20][21][22][23] Clinical trials investigating the use of sequential treatment strategies in mRCC have shown that single targeted agents can cause tumor shrinkage, slow disease progression and demonstrate significant PFS and QoL benefits. [18,24,25] The benefit of targeted therapy second line and beyond in patients with mRCC has been demonstrated through the analysis of data from 2705 patients, obtained from the International mRCC Database Consortium, which indicated that patients who are able to receive more lines of targeted therapy live longer than those who receive fewer.…”
Section: Expert Opinionmentioning
confidence: 99%
“…For example, the Czech Clinical Registry of Renal Cell Cancer Patients (RENIS) is a highly valuable resource, providing information on the treatment of patients with mRCC that is particularly relevant to the CEE region. [20][21][22][23]32] Data of 218 patients with mRCC treated with sunitinib and sorafenib obtained from RENIS showed a strong correlation between responses to first-versus second-line VEGF inhibitor (p < 0.001); however, duration of response on the first-line VEGF-targeted therapy was not a valuable indicator of response to second-line VEGF-targeted therapy. [22] Whereas retrospective analysis of data from the International mRCC Database Consortium on 464 patients with mRCC who had been treated with VEGF inhibitors in the first and second line demonstrated that patients can benefit from second-line VEGF-targeted therapy regardless of the response in first line.…”
Section: Expert Opinionmentioning
confidence: 99%
“…In some cases like the human epidermal growth factor receptor (HER)-2 the target is obvious and its expression on tumor cells represents a biomarker guiding the therapy (2). However, in other cases the definition of biomarkers that would predict response to targeted therapies is more difficult and targeted treatments are selected empirically rather than based on biomarkers (3). This is especially true in the case of immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…For example, apart from circulating VEGF there are still no predictive biomarkers for drugs targeting VEGF or VEGF receptors that currently represent the backbone of therapy in some tumors, e.g., metastatic renal cell carcinoma [58] , and these therapies are currently prescribed more or less indiscriminately. While most assays used either tumor tissue or peripheral blood (including plasma or serum) as the sample matrix for biomarker determination, methods have been introduced to determine tumor biomarkers in cerebrospinal fluid [59 -61] , urine [62 -64] , stool [65] , secretions [66] or breath [67 -69] .…”
Section: Tumor Markers -The Old and The Newmentioning
confidence: 99%